THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE AND TRAINING OF EMPLOYEES REFILL DRINKING WATER DEPOTS WITH IMPLEMENTATION OF SANITATION HYGIENE REFILL DRINKING WATER DEPOTS IN THE WORKING AREA OF KENALI BESAR PUBLIC HEALTH CENTER - Siti Manna Nasution; Andy Amir; Fajrina Hidayati (International Journal of Medicine and Health, 2023)
Based on data from the Jambi Provincial Health Office in 2021 drinking water depots that meet health requirements have not reached the target of 92.6% of the 100% target. Sanitary hygiene is an effort made to control the risk factors for contamination of drinking water. The purpose of this study was to find out the relationship between knowledge, attitudes, and training with the implementation of sanitation hygiene at the drinking water depot in the working area of ​​the Kenali Besar Health Center in 2022. This research uses a quantitative research design with a cross-sectional research design. The research was conducted in the working area of ​​the Kenali Besar Health Center in August-February 2023. The population and samples of this study were 51 employees of the Kenali Besar Health Center (DAMIU) in the Work Area of ​​the Kenali Besar Health Center. The results of the study showed that the application of sanitation hygiene was in the proper category (52.9%). The statistical test results showed that the variables were knowledge (p=0.000 <0.05), attitude (p=0.000 <0.05), and training (p=0.01 <0.05). Concusion, there is a relationship between knowledge, attitudes, and employee training with the application of sanitary hygiene at refill drinking water depots (DAMIU) in the Working Area of ​​the Kenali Besar Health Center